Assessment of surface water and groundwater potential under climate change in the Lam Phaniang River Basin - Savayo, Joonlaykha; Saraphirom, Phayom; Homtong, Nudthawud; Kangrang, Anongrit; Kuntiyawichai, Kittiwet (Engineering and Applied Science Research, 2025)
The assessment of surface water and groundwater potential under climate change in the Lam Phaniang River Basin was based on SWAT model for evaluating streamflow, and MODFLOW model for evaluating groundwater flow. The SWAT model was well calibrated and validated with daily discharge measured at E.68A during 2010-2015 and 2016-2021, respectively, with R2 and Nash-Sutcliffe Efficiency values more than 0.60. The MODFLOW model was also well calibrated and validated with observation data from 16 groundwater wells during May 2021, and 2 groundwater observation wells of Department of Groundwater Resources during 2013-2021, respectively, with r greater than 0.95 and Normalized Root Mean Square Error less than 10%. Future climate analysis (2022-2099) was based on Regional Climate Models (CNRM-CM5, CanESM2, and GFDL-ESM2M), under RCPs 4.5 and 8.5 scenarios. The maximum and minimum temperatures under RCP 4.5 were 34.54 °C and 21.07 °C, respectively, while under RCP 8.5, both temperatures were 35.30 °C and 20.36, respectively. The future mean temperature tended to be higher than present temperature (32.35 °C and 19.28, respectively). The future mean annual rainfall, which were 1,246.37 mm/year and 1,250.01 mm/year under RCPs 4.5 and 8.5, respectively, were lower than the mean annual rainfall recorded between 2002-2021 (1,257.00 mm/year). The surface water under RCPs 4.5 and 8.5 were lower than the present condition (2,175,988,582 m3/year), while the future groundwater supply was increased from the present (424,418,714 m3/year). When annual surface water supply was compared with water demand, no water shortage was expected under present condition, while low to moderate levels of water shortage were identified under RCPs 4.5 and 8.5. When compared annual surface and groundwater supply with the demand, no water shortage was detected under present and future conditions. Finally, the obtained results will be useful for surface and groundwater management, in which water-related problems can sustainably be solved.